2013
DOI: 10.5194/angeo-31-107-2013
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of orographic forcing on TC Dina (2002) in South West Indian Ocean

Abstract: Abstract. Using the French non-hydrostatic mesoscale numerical model Méso-NH, intense tropical cyclone (TC) Dina (2002) is simulated to investigate the forcing caused by the steep orography of Réunion island (20.8 • S, 55.5 • E) in the southwest Indian Ocean. The model initialised by a bogus vortex derived from Doppler radar observations reproduces quite well the dynamical characteristics of TC Dina approaching the island and provides some clues on the orographic influence on the structure and the evolution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Several MESO‐NH simulations have been successfully performed over Reunion Island at different resolutions to study cyclone formation or pollutant transport [ Tulet and Villeneuve , ; Lesouëf et al ., , ; Jolivet et al ., ; Durand et al ., ; Sivia et al ., ; Vérèmes et al ., ]. The model was set up with four two‐way nested domains having horizontal grid spacing of 16, 8, 2, and 0.5 km and grid size of 200 × 200, 128 × 128, 128 × 128, and 192 × 160 points, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several MESO‐NH simulations have been successfully performed over Reunion Island at different resolutions to study cyclone formation or pollutant transport [ Tulet and Villeneuve , ; Lesouëf et al ., , ; Jolivet et al ., ; Durand et al ., ; Sivia et al ., ; Vérèmes et al ., ]. The model was set up with four two‐way nested domains having horizontal grid spacing of 16, 8, 2, and 0.5 km and grid size of 200 × 200, 128 × 128, 128 × 128, and 192 × 160 points, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Several MESO-NH simulations have been successfully performed over Reunion Island at different resolutions to study cyclone formation or pollutant transport [Tulet and Villeneuve, 2011;Lesouëf et al, 2011Lesouëf et al, , 2013Jolivet et al, 2013;Durand et al, 2014;Sivia et al, 2015;Vérèmes et al, 2016] First, we will use the FLEXPART (FLEXible PARTicle dispersion model) Lagrangian particle dispersion model to assess air masses origin and transport pathways. We will focus on May 2015 to take advantage of the Maïdo ObservatoRy Gaz and Aerosols Ndacc Experiment (MORGANE) field campaign that started in May [Duflot et al, 2017].…”
Section: Evolution Of the Abl Diurnal Variability At The Mo Sitementioning
confidence: 99%
“…It is a nonhydrostatic anelastic model, able to simulate the motion of the atmosphere, at scales ranging from synoptic (hundreds of kilometers) to microscale (tens of meters). Meso-NH has already been successfully used to simulate storms and tropical cyclones (Barthe et al, 2016;Chane-Ming et al, 2014;Jolivet et al, 2013;Nuissier et al, 2005;Pantillon et al, 2013Pantillon et al, , 2015Pantillon et al, , 2016.…”
Section: Presentation Of the Modeling Systemmentioning
confidence: 99%
“…In previous studies, the model proved to be useful for the simulation of cyclones' development. Nuissier et al (2005) Roux et al (2004), was numerically examined in Jolivet et al (2013). In particular, PV estimates revealed that buoyancy waves were generated on the lee side of the island's peak (3070 m) when peripheral cyclonic flow of the TC impacted on the island.…”
Section: Model Descriptionmentioning
confidence: 99%